Risk Perception and Risk Communication for Training Women Apprentice Welders: A Challenge for Public Health Nursing - Clarice Alves Bonow; Marta Regina Cezar-Vaz; Marlise Capa Verde de Almeida; Laurelize Pereira Rocha; Anelise Miritz Borges; Diéssica Roggia Piexak; Joana Cezar Vaz (Nursing Research and Practice)
This research has aimed to identify the perceptions of women apprentice welders about physical, chemical, biological, and physiological risk factors to which they are exposed and evaluate the identification of health disorders self-reported for women apprentice welders before and after implementation of a nursing socioenvironmental intervention. A quantitative study was performed with 27 women apprentice welders (first phase) and before and after an intervention with 18 women (second phase) in Southern Brazil in 2011. The data were analysed using SPSS 19.0. The participants identified the following risk types: physical (96.2%), chemical (96.2%), physiological (88.8%), and biological (62.9%). The results show a significant difference of the pre- and posttest averages for the musculoskeletal system and a posttest average increase for the integumentary, respiratory, and auditory system. A correlation of the women apprentices’ ages and the identification of health disorders were made. It was understood that the perception of women apprentices regarding a particular set of occupational risks is essential for public health nursing to develop an effective risk communication as a positive tool for teaching and learning.